2009
DOI: 10.1136/bmj.b2060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for births booked under an independent midwife and births in NHS maternity units: matched comparison study

Abstract: Objective To compare clinical outcomes between women employing an independent midwife and comparable pregnant women using NHS services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 22 publications
1
35
0
4
Order By: Relevance
“…Women with defined antenatal risk factors were still eligible for at least some care at the FMU, and uptake of this amongst "higher risk" women is very high. Our findings reflect other studies and reviews of "non-standard" antenatal care (Symon et al 2009;Allen et al 2012;Sandall et al 2013). While observational studies are low in the hierarchy of research evidence, our findings do appear to be a further indicator that there may be something in the antenatal care model which affects the likelihood of preterm birth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Women with defined antenatal risk factors were still eligible for at least some care at the FMU, and uptake of this amongst "higher risk" women is very high. Our findings reflect other studies and reviews of "non-standard" antenatal care (Symon et al 2009;Allen et al 2012;Sandall et al 2013). While observational studies are low in the hierarchy of research evidence, our findings do appear to be a further indicator that there may be something in the antenatal care model which affects the likelihood of preterm birth.…”
Section: Discussionsupporting
confidence: 83%
“…A non-statistically significant difference in preterm birth rates (4% vs. 6%) was found in Tracy et al"s (2013) comparison of "caseload" and "standard" midwifery care. A finding of a highly significant difference in preterm birth rates was also found in a matched cohort study comparing clinical outcomes for women receiving "standard" National Health Service (NHS) care and women employing an independent midwife (Symon et al 2009); 87% of the latter were planning a homebirth [66% achieved this]. In that study results were adjusted for several risk factors including medical and previous obstetric complications, so off-setting one of the criticisms levelled at evaluations of "non-standard" antenatal care packages -that they focus principally on birth outcomes for "low-risk" women (cf.…”
Section: England and Wales In 2006 Was £295 Billion (Us$457 Bn)mentioning
confidence: 73%
“…Homebirth for low-risk women attended by registered midwives, is just as safe as hospital birth and is gradually becoming a more acceptable birth option being offered to women by mainstream maternity services throughout Australia (Catling-Paull et al, submitted for publication). The majority of the scientific evidence and health policy however consider intentional birth at home without the presence of a health professional (freebirth) (Newman, 2008, p. 451) or planned homebirth for higher risk pregnancies, as less safe (Bastian et al, 1998;Dahlen, 2009;Symon et al, 2009;Kennare et al, 2010;Wax et al, 2010). There is some evidence that both freebirth and high risk home birth are becoming more common in Australia than they once were (Newman, 2008;Dahlen et al, 2010;Dahlen et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, even if they are planning a home birth, most women receive antenatal, intrapartum and postnatal care from health professionals directly employed by a specific hospital (except those employing an independent midwife; this is rare (12)). UK vital registration data have revealed regional variations in take-up of home birth (7) and previous research has identified wide variations in home birth rates between NHS Trusts in England, even when rates were adjusted for age and parity (13).…”
Section: Introductionmentioning
confidence: 99%